Relationship between diagnostic imaging features and prognostic outcomes in gastrointestinal stromal tumors (GIST) - Danti, Ginevra; Addeo, Gloria; Cozzi, Diletta; Maggialetti, Nicola; Lanzetta, Monica Marina; Frezzetti, Gianluca; Masserelli, Antonella; Pradella, Silvia; Giovagnoni, Andrea; Miele, Vittorio (Acta Biomedica Atenei Parmensis, 2019)
Gastrointestinal stromal tumors (GISTs), the most frequent mesenchymal neoplasms of the gastrointestinal tract, are a relatively recently described entity. GISTs can occur across any age but are more common in patients older than 50 years. GISTs most commonly are in the stomach (60-70%), followed by the small intestine (20%-30%); they also rarely occur in the abdominal cavity, such as in the mesentery, the omentum and the retroperitoneum. Contrast-enhanced multi-detector computed tomography (MDCT) is the most largely used imaging modality for the localization, characterization and staging of GISTs. All patterns of enhancement on contrast-enhanced MDCT can be seen with GISTs, including hypoenhancing, isoenhancing, and hyperenhancing neoplasms. A lot of prognostication systems have been proposed for the risk stratiﬁcation of GISTs. This review outlines the relationship between different diagnostic imaging features and prognostic outcomes in GISTs.